ANALISIS GERAK JATUH BEBAS DENGAN METODE VIDEO BASED LABORATORY (VBL) MENGGUNAKAN SOFTWARE TRACKER - Agung Ristiawan (UIN Sunan Gunung Djati Bandung, 2018)
The purpose of this study is to determine the magnitude of the gravitational acceleration in free fall motion analyzed by the Tracker and determine the magnitude of the acceleration of free-falling objects depending on the magnitude of the force affecting the object by varying the distance the object is dropped. Retrieval of data in this study through experiments in Catur Tunggal, Yogyakarta. The subject of this research is the large acceleration of free-falling body motion. In the free fall motion variations in the height of falling objects by 40, 50, 60, 70, 80, 90, and 100 cm for the same mass of objects that is 353 grams. The data needed is the position of the load on the free fall through Tracker analysis conducted on the recorded video. To find out the magnitude of the velocity and the magnitude of the frictional force acting on free fall motion an analysis is performed using a predetermined equation. The effective time in this study is two months. Based on the Tracker analysis, a velocity graph of linear time is obtained, from the graph the acceleration of free falling objects obtained by the equation obtained in the linear graph is Y = mt + b, where m is the gradient of the linear graph showing the acceleration obtained by analyzing Tracker is the same as gravitational acceleration in theory and for free fall motion of objects obtained an average acceleration of (9,63 ± 0,33) m/s2.